Design and development of a casual mobile game (A) - Rahardja, Calista (Nanyang Technological University, 2021)
This project was undertaken with the intention of designing and developing a casual mobile game simulating daily life while simultaneously dealing with the fallout from the current global pandemic. As a team of three, we decided to use an alternate fantasy reality to juxtapose against our realistic experiences, and each played different roles with regards to this project, ranging from brainstorming ideas, graphic design, and final development. The game is implemented using the Unity2D Game Engine (2020.1.8f1), with its graphics digitally illustrated in Procreate 5.